Baltic Pathways from Liberal Trade Model to Neo-Mercantilism in the European Union - Viljar Veebel (Managing Global Transitions, 2015)
The economic progress of the Baltic States after the restoration of independence has been closely related to the liberal ideology and values of their economies: openness to investments, simple tax system and low tax burden, liberal trade policy, and flexible labour market. Unlike the Baltic States, some of their main partners in the European Union (EU) have focused on promoting their economic growth by the neo-mercantilist way of expanding exports, supported by the economic structure of these countries exporting high technology and capital goods. As a result, when the Baltic States are expecting that in a broader context the other eu member states share the same vision of the liberal market economy, their motives have not been fully understood among their regional trade and cooperation partners. Current study will debate whether the practical implementation and needs of the European neo-mercantilism meet the economic and social needs of the Baltic States. Additionally, the study focuses on the question whether in practice the Baltic countries should be ready for the European neo-mercantilist project in upcoming years.